Tinjauan Kritis Ritual Sangiang dalam Perspektif Kristianidi Paroki Santo Fransiskus Parengean Assisi - Bagus Nurlistyawan; Megan julian (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2024)
This study aims to find out the view of Dayak Ngaju Catholics about Sangiang Rituals, their appreciation about the sacrament of anointing the sick, and the implementation comparison about the sacrament of anointing of the Sick and rituals of Sangiang in Ngaju Dayak culture. The method used in this study is qualitative research methods. Data is obtained by interview, observation and documentation. The data obtained were analyzed using Miles and Huberman steps used through data reduction, data presentation and conclusion drawing. The results of the study show that Dayak Ngaju people know about the Sangiang ritual as a healing ritual in Dayak Ngaju’s culture. The people know about the sacrament of the anointing of the sick in the Catholic Church as one of the sacraments asking that the sick person is strengthened in order to be able to pass through all his illnesses because of God's help.This conclusion is that the sangiang ritual has a social dimension that directs, and brings people to realize that to live together requires a sense of caring between one another. The values contained in the sangiang ritual are values of togetherness and brotherhood. The presence of the Church in the culture is the entrance to proclaiming the kingdom of God, especially giving catechesis related to the sacrament of anointing the sick because God himself works to heal especially in the sangiang ritual.